IMPLEMENTASI KEBIJAKAN PENGALIHAN KEWENANGAN SEKOLAH LUAR BIASA (SLB) NEGERI UNGARAN DARI PEMERINTAH KABUPATEN SEMARANG KEPADA PEMERINTAH PROVINSI JAWA TENGAH - Fajri, Hajiriyan Yusuf; Purnaweni, Hartuti (Journal of Public Policy and Management Review, 2018)
Special education in this case School for the Disable (SLB) is one of the educational institutions whose management is transferred from the authority of Regency/City Government to the authority of Provincial Government since the enactment of Law Number 23 Year 2014 on Regional Government. Central Java Provincial Government took over the management of all the School for the Disable (SLB) in 33 Regency/Cities, one of which is the Special School of Ungaran. Several aspects of authority submitted to the Central Java Provincial Government are personnel, funding, facilities and infrastructure, as well as documents. The purpose of this research is to know the policy implementation of transfer authority of School for the Disable (SLB) of Ungaran from Government of Semarang Regency to Central Java Provincial Government. The approach used is descriptive qualitative with data collection technique through interview, observation, and documentation. To assess the policy implementation of transfer authority of School for the Disable (SLB) of Ungaran from the Semarang Regency Government to the Central Java Provincial Government, the Effectiveness of Policy Implementation is policy precision, accuracy of the implementer, target precision, environmental precision and process accuracy. The result of the research shows that the policy of transfer of authority School for the Disable (SLB) of Ungaran from Semarang Regency Government to Central Java Provincial Government can solve the problem of unclear management of special education although there is no regulation as technical guidance in implementing the policy, Semarang Regency Government has handed over the management School for the Disable (SLB) of Ungaran to the Provincial Government. It is recommended that the implementer immediately develop a regulation that can be used as a technical implementation guide.